Heute, so ihr seine Stimme höret: Predigten, gehalten in der Klosterkirche in Cottbus - Jacob, Günter (Dienst am Wort, 1959)
1. Lk 05:01-11 - Jacob, Günter (Predigt), 2. Apg 20:17-38 - Jacob, Günter (Predigt), 3. Kor <1> 04:01 - Jacob, Günter (Predigt), 4. Kön <2> 05:01-19a - Jacob, Günter (Predigt), 5. Lk 10:17-19 - Jacob, Günter (Predigt), 6. Lk 01:46-55 - Jacob, Günter (Predigt), 7. Lk 02:25-32 - Jacob, Günter (Predigt), 8. Lk 01:68-79 - Jacob, Günter (Predigt), 9. Mk 15:39 - Jacob, Günter (Predigt), 10. Petr <1> 01:03 - Jacob, Günter (Predigt), 11. Joh 12:20-26 - Jacob, Günter (Predigt), 12. Tit 03:04-07 - Jacob, Günter (Predigt), 13. Lk 09:51-56 - Jacob, Günter (Predigt), 14. Joh 12:01-08 - Jacob, Günter (Predigt), 15. Lk 01:26-38 - Jacob, Günter (Predigt), 16. Mt 25:01-13 - Jacob, Günter (Predigt), 17. Apg 08:26-39 - Jacob, Günter (Predigt), 18. Joh 06:01-15 - Jacob, Günter (Predigt), 19. Lk 24:13-35 - Jacob, Günter (Predigt), 20. Mk 10:13-16 - Jacob, Günter (Predigt), 21. Apg 10:42-48 - Jacob, Günter (Predigt), 22. Mt 02:01-12 - Jacob, Günter (Predigt)